Prognostic predictors for patients with hepatocellular carcinoma receiving adjuvant transcatheter arterial chemoembolization. Issue 7 (July 2019) - Gu, Jingxian; Zhang, Xing; Cui, Ruixia; Zhang, Jia; Wang, Zhixin; Jia, Yifan; Miao, Runchen; Dong, Yanyan; Ma, Xiaohua; Fan, Haining; Wang, Haijiu; Ren, Li; et al.
Abstract : Objectives: We aimed to confirm the clinical effectiveness of postoperative adjuvant transcatheter arterial chemoembolization (PA-TACE) in patients with hepatocellular carcinoma after liver resection, and further identify the patients who could benefit most from PA-TACE. Patients and methods: Propensity score matching at a ratio of 1 : 2 was used between hepatectomy patients with and without receiving PA-TACE. Kaplan–Meier analysis was performed to compare overall survival and recurrence-free survival between two groups. Univariate COX regression and stratified analyses were performed to screen and identify survival predictors for PA-TACE patients. The identified predictive markers were validated in an external cohort. Results: The propensity analysis matched 116 patients in PA-TACE group to 232 in the control group. Visible protective effect of PA-TACE was shown by survival curves in matched series (log-rank P =0.009 and 0.008), with hazard ratio of being 0.599 (95% confidence interval: 0.420–0.855) and 0.623 (95% confidence interval: 0.449–0.866), respectively, for overall survival and recurrence-free survival. The identified prognostic predictors for PA-TACE included TNM stage, tumor size and number, hepatitis B infection, spleen diameter, preoperative serum α-fetoprotein, alkaline phosphatase, γ-glutamyl transpeptidase and monocyte, and three risk signatures (aspartate aminotransferase-to-alanine aminotransferase ratio, neutrophil-to-lymphocyte ratio, and systemic immune-inflammation index). Conclusion: The treatment effectiveness of adjuvant transcatheter arterial chemoembolization for patients with hepatocellular carcinoma after surgery was validated in this study, and the best candidates for PA-TACE were identified as well, including patients with late-stage tumor, portal hypertension, and high preoperative serum levels of α-fetoprotein, alkaline phosphatase, γ-glutamyl transpeptidase, and monocytes. Abstract : Supplemental Digital Content is available in the text.